As mulheres e o meio ambiente, no romance Terras do Sem Fim, de Jorge Amado - Rocha, Eny Araújo (2014)
The current dissertation has, for its objective, the investigation of Jorge Amado's work Terras do sem fim, in the light of the philosophical principles of Ecofeminism. This project demonstrates the relation between the environment and the female character inserted in the patriarchal system of the cacaueiran society, in the south of Bahia, in the beginning of the XX century. To achieve this objective, two philosophical lines will be used, namely: 1) The spiritualist ecofeminism, promoted by Maria Mies and Vandana Shiva; 2) the care ethics, created by Karen J. Warren. Amado's work will be analyzed with the goal of discovering the feminine behavior and pondering about the transgressor aspect of such a relation with the environment, reciprocal in its own nature, as the environment also manifest itself when it feels threaten by its dominator. For method of analysis, the bibliographical research of a wide-range of fields, including Literature, Sociology, Philosophy and Ecofeminism, was used in this study. The research is divided in three chapters. In the first, the novel Terras do sem fim will be characterized in the regionalist movement of the 1930s and the critical response of this work will also be used. The second chapter aims to justified and elaborate the ecofeminists principles used in this analytical and critical investigation. Finally, in the third chapter, the ecofeminists principles will be used to analyze the female characters and their transgressions connected to the environment, under the regime of the patriarchal system. The conclusion of the work tries to show that the novel Terras do sem fim has, in its literary structure, the opening of a critical discussion not presented in its time of publishing, bringing a wider perspective into the studies of Ecofeminism.